2017
DOI: 10.1186/s12864-017-3913-1
|View full text |Cite
|
Sign up to set email alerts
|

Associating mutations causing cystinuria with disease severity with the aim of providing precision medicine

Abstract: BackgroundCystinuria is an inherited disease that results in the formation of cystine stones in the kidney, which can have serious health complications. Two genes (SLC7A9 and SLC3A1) that form an amino acid transporter are known to be responsible for the disease. Variants that cause the disease disrupt amino acid transport across the cell membrane, leading to the build-up of relatively insoluble cystine, resulting in formation of stones. Assessing the effects of each mutation is critical in order to provide ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
(56 reference statements)
2
18
0
1
Order By: Relevance
“…[2] The recently published literature review on a set of 94 SLC3A1 and 58 SLC7A9 point mutations known to be associated with cystinuria has shown that there were differences in sequence location, evolutionary conservation, allele frequency, and predicted effect on protein function between these mutations and other genetic variants of the same genes that occur in a large population. [3] Interestingly, the case in question supports the few published anecdotal studies on the absence of mutations in many patients with cystinuria. Obaid et al found in their studied case series on Saudi patients with cystinuria that two out of eight patients had negative molecular testing.…”
supporting
confidence: 65%
“…[2] The recently published literature review on a set of 94 SLC3A1 and 58 SLC7A9 point mutations known to be associated with cystinuria has shown that there were differences in sequence location, evolutionary conservation, allele frequency, and predicted effect on protein function between these mutations and other genetic variants of the same genes that occur in a large population. [3] Interestingly, the case in question supports the few published anecdotal studies on the absence of mutations in many patients with cystinuria. Obaid et al found in their studied case series on Saudi patients with cystinuria that two out of eight patients had negative molecular testing.…”
supporting
confidence: 65%
“…Most mutations identified in cystinuria are missense mutations leading to the change of a single amino acid in the protein. The effect of these mutations can range from having no effect on protein function to loss of function [ 183 ]. It is estimated that approximately 99% of cationic amino acids are reabsorbed at the apical membrane of proximal kidney tubules [ 96 , 97 ], indicating that b 0,+ AT-rBAT mediated transport may have a considerable leverage on the homeostasis of cationic amino acids.…”
Section: Transporter Families Shown To Transport L-arginine And/ormentioning
confidence: 99%
“…Based on cystine crystalluria analyses, we suggest for the first time that the target of urine specific gravity should be ≀ 1.005 and we confirm that patients should maintain urine pH > 7. 5…”
Section: Discussionmentioning
confidence: 99%
“…Cystinuria (OMIM 220100), a genetic defect of cystine tubular reabsorption, is responsible for 1% of nephrolithiasis cases in adults and between 8% and 10% of cases in children . Cystinuria is caused by mutations in SLC3A1 or SLC7A9 genes, encoding, respectively, for the subunits rBAT and b0, +AT of an amino acid transporter B0 . Because of the poor solubility of cystine at urine pH <7, cystinuria results in stone formation.…”
Section: Introductionmentioning
confidence: 99%